(untitled) - Witham, Francis H. (Boston, 1986)
Exercises intended for use in a one or two term course in introductory plant physiology. Exercises vary in content and complexity and present a broad spectrum of basic physiological concepts and techniques.
Keywords: Plant physiology,Sinh lý học thực vật; Laboratory manuals,Tài liệu phòng thí nghiệm